The Content And Essence Of Subject Integration In The Teaching Of Mother Language And Reading Literacy In Primary Language Education - pcadmin, Inayat Elmurodova; Khushbok B. Narbutaev (Global Scientific Publishing, 2025)
This article is about the native language and reading literacy subjects in the classrooms Improvement in the content of interdisciplinary integration, application of methods for implementing mechanisms for ensuring the content and quality of the scientific and methodological process of teaching to the pedagogical process carried out, identifying and improving the content, form, methods and means of teaching based on the integration of subjects, as well as the effectiveness indicators of teaching first-grade subjects, practical significance, opportunities for effective use of the results obtained , native language and reading literacy subjects in the classrooms The content of the learning process is described in terms of interdisciplinary integration, improvement, and application of previously acquired theoretical knowledge, practical skills, qualifications, and competencies in academic subjects in new situations.
Keywords: primary school; students; interdisciplinary integration